Polymorphism Of Caprine Lymphocyte Antigen-Drb3 Gene By Pcr-Rflp In Goats - Yadav, Alok Kumar; Tomar, S. S.; Kumar, Amit; Thakur, M. S. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Polymorphism of exon 2 of caprine lymphocyte antigen-DRB3 (CLA-DRB3) gene was investigated in Sirohi and Barbari goats. Genomic DNA isolation, quantification and standardization of PCR protocol was done as per standard methodologies. The restriction digestion of PCR product was performed using enzymes PstI. Exon 2 of CLA-DRB3 was found to be polymorphic in both the breeds. Two alleles (A and B) and three genotypes (AA, AB and BB) were observed in the samples of both the breeds under study. The genotype frequencies of AA, AB and BB were 0.53, 0.37 and 0.10, respectively in Sirohi and 0.73, 0.20 and 0.07 in Barbari breed. The frequencies of A and B alleles were 0.72 and 0.28 in Sirohi and 0.83 and 0.17 in Barbari breed, respectively. Both the breeds were in Hardy-Weinberg equilibrium for these variants and were homogeneous with respect to their distribution.
Keywords: Barbari; CLA-DRB3 gene; PCR-RFLP; Sirohi